CHARACTERISTICS OF ACTIVITIES OF STUDY AND ANALYSIS OF CRIMINOGENIC SITUATION IN THE ADMINISTRATIVE AREA OF PREVENTION INSPECTOR - Jalilov Nodirbek Komil oglu (Scholar Express Journal, 2022)
The article describes the specifics of the activities of the prevention inspector to study and analyze the criminogenic situation in the administrative territory, the scientific and practical significance of the study of the criminogenic situation, what is the study and analysis of the criminogenic situation and its procedure, content, Legal basis for the study and analysis of the criminogenic situation in the region, prevention inspectors to identify the causes and conditions of the criminogenic situation and cooperation with other government agencies in their elimination activities, prevention inspectors to identify the causes and conditions of the criminogenic situation and measures to eliminate them. The circumstances of the event were scientifically analyzed and appropriate proposals were made in this regard
Keywords: Prevention Inspector; Administrative Area; Public Safety; Criminogenic Situation